Rheological and Flocculation Analysis of Microfibrillated Cellulose Suspension Using Optical Coherence Tomography - Koponen, Antti I.; Lauri, Janne; Haavisto, Sanna; Fabritius, Tapio (Applied sciences, 2018)
A sub-micron resolution optical coherence tomography device was used together with a pipe rheometer to analyze the rheology and flocculation dynamics of a 0.5% microfibrillated cellulose (MFC) suspension. The bulk behavior of the MFC suspension showed typical shear thinning (power-law) behavior. This was reflected in a monotonously decreasing floc size when the shear stress exceeded the yield stress of the suspension. The quantitative viscous behavior of the MFC suspension changed abruptly at the wall shear stress of 10 Pa, which was reflected in a simultaneous abrupt drop of the floc size. The flocs were strongly elongated with low shear stresses. With the highest shear stresses, the flocs were almost spherical, indicating a good level of fluidization of the suspension.